(untitled) (History Journal «Jerónimo Zurita», 2025)
Until the 19th century, the taking of economic reprisals between nations transcended the concept of revenge as it was the result of a considered decision by the jurisdictional authority and was also subject to certain limiting rules. Given the lack of ordering of military reprisals linked to the treatment of prisoners, it was assumed that they followed the same system as commercial reprisals linked to international law. The exalted Spaniards of the first third of the century emptied these control measures of their content, resulting in the creation of revolutionary institutions. The new rules, no longer limited the law, but rather ritualized it at a time when a concatenation of civil wars in our country was going to turn the extraordinary into the everyday.